Phase Formation Sequence in Combustion of Pressed Aluminum Nanopowder in Air Studied by Synchrotron Radiation; Combustion, Explosion and Shock Waves; Vol. 49, № 3 - Il'in A. P. (2013, 2013)
The intermediate and final combustion products of pressed aluminum nanopowder arestudied. It is found that the main combustion product is aluminum nitride. In the intermediatestages of combustion, aluminum oxide (γ-Al2O3) and oxynitride (Al5O6N) are the first to formon the sample surface, and aluminum nitride is formed next. The use of sliding (incident at asmall angle to the surface) synchrotron radiation made it possible to determine with high accuracy(in time) the sequence of stages of formation of crystalline products during combustion of thealuminum nanopowder.